(3eYGfi MQha GdgLGAs - (3GdNdjd Hf CMeO Hf YeQh Hf Jeje GdaQGgjOj GdCROj GdjMeOj, CHh YHO GdQMef,J (B170 (3g` s
(3ChdgG (B:s
(3bGd GdNdjd Hf CMeO GdHUQi QMeI Gddg JYGdi hQVi Yfg GdCda gh GdaQO ef GdQLGd hbjd gh GdQLd GdZQjH s
(3BNQgG (B:s
(3bGd GdTGYQ (B: (3JjeeJ jGA GdMi deG dbjJgG JVF cHO hWGdY djdI GdbOQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B112s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs